2020
DOI: 10.1186/s42269-020-00416-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous salicylic acid or indole acetic acid on their endogenous levels, germination, and growth in maize

Abstract: Background Exogenous hormone applications modify the plant growth and development by inducing changes in their endogenous contents. However, it is not clear whether the effects of exogenous hormones on growth are direct or related with changes induced in endogenous hormones. Laboratory and greenhouse experiments were conducted to study the effect of exogenous salicylic acid (SA) or indole acetic acid (IAA) on endogenous levels in soaked seeds, 5-day-old seedlings, and in vegetative growth of foliar-sprayed pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In a comparative study, El-Mergawi and El-Wahed [ 92 ] conducted a greenhouse experiment to determine how foliar sprays of IAA or salicylic acid (SA) affect maize plant growth and the concentrations of endogenous IAA and SA. They reported that spraying plants with IAA and SA (0.25–2 mM) significantly increases the endogenous content of IAA and SA in a concentration-dependent manner, and the maximum increase (10–34%) was recorded after two days of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…In a comparative study, El-Mergawi and El-Wahed [ 92 ] conducted a greenhouse experiment to determine how foliar sprays of IAA or salicylic acid (SA) affect maize plant growth and the concentrations of endogenous IAA and SA. They reported that spraying plants with IAA and SA (0.25–2 mM) significantly increases the endogenous content of IAA and SA in a concentration-dependent manner, and the maximum increase (10–34%) was recorded after two days of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…in cucumber under salt stress 31 and in Baikal skullcap under salt and drought stress 51 . Exogenous application of salicylic acid induced both IAA and SA in maize and cucumber under drought stress 52,53 .…”
Section: Resultsmentioning
confidence: 99%
“…Also, 24 of 30 KH family genes contain ABA-responsive cis -elements (ABRE, AACCCGG), which indicated some KH family genes such as AtKH1 , AtKH9 can respond to ABA through these cis -elements. ABA and SA are the important hormones in plants, which are involved in diverse processes, such as germination and adaptation to different stresses [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be produced when plants are exposed to drought, cold, or high osmotic pressure [ 23 , 24 ]. SA can promote seed germination under high salt concentration and osmotic pressure [ 25 ], while the highest concentration of SA inhibits the germination of maize seeds [ 26 ]. However, the KH family genes which are a response to ABA and SA are seldom investigated.…”
Section: Introductionmentioning
confidence: 99%